A IDENTIFIKASI LAPISAN AKUIFER BERDASARKAN METODE VERTICAL ELECTRICAL SOUNDING (VES) DI WILAYAH KABUPATEN LOMBOK UTARA - IRMA RISVANA DEWI (Jurnal Inovasi Pendidikan dan Sains, 2023)
: Lombok northern district based on the litological map of lombok island lies in the northern mountains. The aquifer in the region has a narrow flow through the cleft and low point space to moderate. Filling the needs of groundwater resources results in bold vertical electrical surveys to provide information on the region's water potential. Measurements obtained on a surface water measurement can still be used to a depth of 14.35 m (14.35 ft). At this point of measurement there isa potential layer of aquifer at 30.79 -72.24 c.e. and 72. 24-10.1.3 m Based on research, the priority of water removal in the deep aquifers at 60 m below the ground will not affect the groundwater and will be provided by the quality and quantity of groundwater in the region.